PELAYANAN BPJS KESEHATAN: Persepsi Masyarakat Kampung Pengok PJKA Demangan Gondokusuman Yogyakarta - Suisyanto Suisyanto; Siti Solechah (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
This article discusses the services of Health Social Security Administering Bodies (BPJS) Kesehatan. The purpose of this study is to determine the perceptions of the urban poor in the service of BPJS Kesehatan. In this study, the authors used a qualitative method with a case study model. The results showed that in society there are two perceptions of BPJS Kesehatan, namely positive perceptions and negative perceptions. Positive perceptions include: BPJS Kesehatan greatly eases payments, BPJS services are very friendly and familiar, BPJS health insurance cards are very beneficial, Negative perceptions include: less than optimal socialization, long administrative processes, and not all types of diseases are covered by BPJS. In addition, BPJS has a complicated administrative process and long queuing time, limited personnel serving, limited personnel serving, not all costs can be borne by BPJS, and it is difficult to pay installments (economy).